2019
DOI: 10.1038/s41598-019-44498-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Photodynamic Therapy against -Periodontitis-causing Bacteria

Abstract: Periodontitis is initiated by causative bacteria in the gingival sulcus. However, as the lesion is often deep and out of circulation system and biofilm is frequently formed on the bacteria cluster, use of antibacterial agents has been limited and the invasive method such as curettage is thought as an only treatment. Here we designed non-invasive photodynamic therapy (PDT), with the ointment which leads a photosensitizer deliverable into gingival sulcus. We assessed whether 650 nm light-emitting-diode (LED) pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 23 publications
2
28
0
4
Order By: Relevance
“…Because SnSe is a layered material, the influence of the layer number on its Raman scattering has attracted much attention. Park et al [143] revealed significant shifts in Raman peaks of SnSe with the change of layer number by first-principle calculations; the results are shown in Figure 16e. With the increase of thickness, the B 2g and A g 2 vibration modes have a red shift, while the B 3g undergoes a blue shift, with a maximum shift up to 100 cm −1 .…”
Section: Raman Scatteringmentioning
confidence: 94%
See 1 more Smart Citation
“…Because SnSe is a layered material, the influence of the layer number on its Raman scattering has attracted much attention. Park et al [143] revealed significant shifts in Raman peaks of SnSe with the change of layer number by first-principle calculations; the results are shown in Figure 16e. With the increase of thickness, the B 2g and A g 2 vibration modes have a red shift, while the B 3g undergoes a blue shift, with a maximum shift up to 100 cm −1 .…”
Section: Raman Scatteringmentioning
confidence: 94%
“…Reproduced with permission. [143] Copyright 2019, Springer Nature. f) Raman spectra of SnSe recorded from 77 to 450 K. g) Temperature-dependence of SnSe Raman frequency.…”
Section: Raman Scatteringmentioning
confidence: 99%
“…Here, we do not include the group-IV monochalcogenides because their Raman spectral peak shifts have been investigated only theoretically. [81] As revealed in Figure 2h, upon increasing the layer number, all of these Raman spectral peaks shift by only approximately 1-4 cm -1 . For easier identification, the peak differences between the A 1g and E 1 2g modes of TMDCs [75,76] and between the A 1 1g and A 2 1g modes of GaSe [79] and InSe, [79] respectively, have been used as a more obviously differentiated "layer number indicator" because these modes shift in opposite directions upon increasing the layer number.…”
Section: Identifying the Layer Number Of 2d Materialsmentioning
confidence: 86%
“…[73,74] In the case of TMDCs, the out-ofplane A 1g vibration mode stiffens (upshifts) while the in-plane E 1 2g vibration mode softens (downshifts) upon increasing the layer number. [75][76][77] Furthermore, the main Raman spectral peaks of h-BN (G band), [78] GaSe (A 1 1g , E 1 2g , and A 2 1g ), [79] InSe [A 1 1g , E 1 2g , A 1 1g (LO), and A 2 1g ], [79] BP (A 1 g , B 2g , and A 2 g ), [80] and several group-IV monochalcogenides, including SnS, SnSe, GeS, and GeSe (B 1u , B 2g , A 2 g , and E 2 3g ), [81] also undergo an upshift or downshift upon increasing the number of layers from a monolayer to a few layers. Figure 2h summarizes the Raman spectral peak shifts with respect to the layer number for various 2D materials.…”
Section: Identifying the Layer Number Of 2d Materialsmentioning
confidence: 99%
“…A periodontite é uma doença inflamatória de etiologia multifatorial e destrutiva progressiva dos tecidos de suporte, resultante de interações entre produtos bacterianos (Park et al, 2019). Dos patógenos mais importantes que causam doença periodontal, microrganismos complexos, como Aggregatibacter Actinomycetemcomitans, Porphyromonas gengivalis e Treponema denticola, Tannerella forsythia podem ser observadas (Tanner, 2014).…”
Section: Introductionunclassified